Investigating the feasibility of geo-tagged photographs as sources of land cover input data - Antoniou, Vyron; Costa Fonte, Cidália; See, Linda; Estima, Jacinto; Arsanjani, Jamal Jokar; Lupia, Flavio; Minghini, Marco; Foody, Giles M.; Fritz, Steffen (MDPI, 2016)
Geo-tagged photographs are used increasingly as a source of Volunteered Geographic Information (VGI), which could potentially be used for land use and land cover applications. The purpose of this paper is to analyze the feasibility of using this source of spatial information for three use cases related to land cover: Calibration, validation and verification. We first provide an inventory of the metadata that are collected with geo-tagged photographs and then consider what elements would be essential, desirable, or unnecessary for the aforementioned use cases. Geo-tagged photographs were then extracted from Flickr, Panoramio and Geograph for an area of London, UK, and classified based on their usefulness for land cover mapping including an analysis of the accompanying metadata. Finally, we discuss protocols for geo-tagged photographs for use of VGI in relation to land cover applications.